1974
DOI: 10.1073/pnas.71.3.957
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Restoration of the Bursa-Dependent Immune System After Transplantation of Allogeneic Stem Cells into Immunodeficient Chicks

Abstract: Transplantation of allogeneic cells from bursa of Fabricius into cyclophosphamide-treated, immunodeficient chicks resulted in immunological tolerance to donor line skin grafts; graft-versus-host disease did not occur. Allogeneic bursal stem cells taken from 3-day-old donors induced restoration of bursal morphology, of antibody formation to Brucella abortus and of occurrence of pyroninophilic cells and immunoglobulin-bearing cells in the peripheral lymphoid tissues. Secondary response to sheep red blood cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1975
1975
1989
1989

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…The bursal stem cells do not induce any graft-versus-host reaction, and thus their ditTerentiation after transplantation into an allogeneic host can be studied. Observations in our laboratory have repeatedly indicated that allogeneic bursal stem cells home to and proliferate in the bursa, inducing a tolerance of the host towards the donor, but their descendants fail to cooperate with the T cells provided by the host [21,22], These findings are in concert with numerous reports indicating the need for histocompatibility between T and B cells participating in an immune response [9,11], The question has remained open whether primitive B-cell precursors can acquire full immunological maturity within an allogeneic host and only be unable to express it in lack of compatible T cells.…”
mentioning
confidence: 99%
“…The bursal stem cells do not induce any graft-versus-host reaction, and thus their ditTerentiation after transplantation into an allogeneic host can be studied. Observations in our laboratory have repeatedly indicated that allogeneic bursal stem cells home to and proliferate in the bursa, inducing a tolerance of the host towards the donor, but their descendants fail to cooperate with the T cells provided by the host [21,22], These findings are in concert with numerous reports indicating the need for histocompatibility between T and B cells participating in an immune response [9,11], The question has remained open whether primitive B-cell precursors can acquire full immunological maturity within an allogeneic host and only be unable to express it in lack of compatible T cells.…”
mentioning
confidence: 99%
“…The initial data by Seto and Henderson [27] and Lerman and Weidanz[\l,18] that cyclophosphamide (Cy) suppressed humoral immunity in the chicken have been confirmed by numerous investigators [7,20,31,32], Eskola and Toivanen [3,4] reported that three in travenous injections of Cy during the late embryonic period rendered chicks deficient in their humoral im mune response. Water-soluble substances enter the embryo when these substances are applied to the air cell [14].…”
Section: Introductionmentioning
confidence: 79%
“…Se cretory cells may induce B cell differentiation in the bursal microenvironment [9,24,25]. The presence of secretory cells in the bursa of Cy-treated embryos might explain why these bursae are capable of recon stitution with bursae from embryos [2][3][4] or newly hatched chicks [31,32]. The inability of bursal cells from older chicks to reconstitute the bursa of Cytreated chicks would suggest an age-related maturational change in older bursal cells [30], Failure to re constitute the bursae of Cy-treated embryos with bone marrow cells [2] might suggest that Cy eliminated mi croenvironmental elements not replaced by bone marrow cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is universally accepted that genes in the MHC play a crucial role in the functioning of the entire immune system (Simonsen, 1982;Abplanalp, 1979), and genes in the B complex regulate the immune response to a variety of antigens (Hala et al, 1981). Toivanen et al (1974) Maccubbin & Schierman (1983), using relatid inbred lines of chickens which differ primarily at the B complex, showed that in vitro killing of cells transformed by reticuloendotheliosis virus is restricted by the B complex. Wainberg et al (1974) showed that splenocytes from hosts bearing primary Rous sarcomas preferentially recognized, and more efficiently inflicted injury on autochthonous rather than allogeneic neoplastic targets.…”
Section: Immunity To Rous Sarcomasmentioning
confidence: 99%